Left-wing governmental alliance in Portugal, 2015-2019: A way of renewing and rejuvenating social democracy? - Freire, A. (2021)
The 2015-2019 left-wing government alliance in Portugal merits attention for several reasons, of which four stand out. First, because, if it worked well, it may offer a solution to the crisis affecting social-democratic parties by pushing them back to the left. Second, because it may offer the radical left greater influence. Third, because existing studies offering comprehensive overviews of the Portuguese case tend to be descriptive in nature. Fourth, because existing studies that are more analytical and explanatory in nature tend to be rather limited in their scope. This study offers an original contribution in that it uses empirical data and takes a comprehensive, analytical and explanatory approach. We argue that the crisis was an important factor in changing old patterns of coalition politics on the Left in Portugal, both because it brought the socialists and radical left parties together in government, and because these changes were very important in guiding the socialists to shift in their policy orientations. Broadly, we argue that the new patterns of coalition politics on the Left and an increased influence of the radical left on domestic politics offer a means of renewing and rejuvenating social democratic parties in Portugal and elsewhere.